Acrylate-based silver nanocomposite by simultaneous polymerization–reduction approach via 3D stereolithography. (December 2017) - Sciancalepore, Corrado; Moroni, Fabrizio; Messori, Massimo; Bondioli, Federica
Abstract: This study demonstrates the feasibility of printing 3D composite objects based on acrylic photocurable formulations, containing in situ generated silver nanoparticles (AgNPs). In fact, the laser radiation of a commercial stereolithography printer was used to both selectively cure, layer by layer, the acrylic resin and to reduce a silver salt to AgNPs (having dimensions ranging between 10 and 25 nm). The most suitable formulation was developed using silver acetate to obtain 1% by weight of AgNPs in the final 3D structures. The presence of the filler causes an increase in the physical and mechanical properties of the samples that become significantly stiffer and stronger than the pristine matrix. Antibacterial properties and electrical conductivity measurements performed on the printed samples gave promising results for the use of the developed formulation for the building of 3D polymeric structures with improved multifunctional properties. Graphical abstract: Highlights: Nano-composites are printed by stereolithography with in situ formed Ag nanoparticles. Laser radiation is employed to both cure the acrylic resin and to reduce Ag ions. Filler causes an increase in the physical and mechanical properties of the samples.